An [Mn2(bpmp)]3+ complex as an artificial peroxidase and its applications in colorimetric pyrophosphate sensing and cascade-type pyrophosphatase assay. Issue 8 (30th January 2018) - Lee, Youngkeun; Yoo, Soyeon; Kang, Seungyoon; Hong, Sukwon; Han, Min Su
Abstract : An [Mn2 (bpmp)] 3+ complex was developed as an artificial peroxidase and applied to colorimetric PPi detection and cascade-type PPase assay. Abstract : The development of artificial peroxidases has attracted great interest because of their applications in various fields such as the chemical industry and biosensing. In this study, 2, 6-bis[(bis(2-pyridylmethyl)amino)-methyl]-4-methylphenol (H-bpmp) complexes with various transition metal ions have been investigated as artificial peroxidases. Among these metal complexes, the [Mn2 (bpmp)] 3+ complex showed the highest peroxidase-like activity as determined by a colorimetric assay using 2, 2′-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) and H2 O2 . The peroxidase-like activity was inhibited by pyrophosphate (PPi), which blocked the active site of the [Mn2 (bpmp)] 3+ complex. Based on this phenomenon, the ABTS/H2 O2 /[Mn2 (bpmp)] 3+ system could be applied for the detection of PPi, which could be achieved selectively by visual observation with a detection limit of 130 nM. Moreover, the addition of pyrophosphatase (PPase) to the [Mn2 (bpmp)] 3+ complex blocked by PPi resulted in the recovery of the peroxidase-like activity of the [Mn2 (bpmp)] 3+ complex due to the hydrolysis of PPi. Hence, the enzyme cascade reaction of the PPase and [Mn2 (bpmp)] 3+ complex allowed the real-time colorimetric assay of PPase.